Environmental factors predicting fish community structure in two neotropical rivers in Brazil - Súarez, Yzel Rondon; Petrere Júnior, Miguel [UNESP] (Sociedade Brasileira de Ictiologia, 2007)
Com o objetivo de identificar os padrões de organização das comunidades de peixes dos rios Jogui e Iguatemi nós amostramos peixes através de redes de espera trimestralmente entre Novembro/1999 e Agosto/2000. Hypostomus ancistroides e Parauchenipterus galeatus foram as espécies de peixes mais abundantes nos rios Jogui e Iguatemi, respectivamente. A variação longitudinal foi mais importante que a sazonal na determinação da composição de espécies em ambos os rios e a diferença entre estações não foi significativa. A altitude foi o fator mais importante na determinação da distribuição das espécies.

In order to assess the organization patterns of the fish communities in the Jogui and Iguatemi rivers, we collected fish with gill nets tri-monthly from November 1999 to August 2000. Hypostomus ancistroides and Parauchenipterus galeatus were the most abundant species in the Jogui and Iguatemi rivers, respectively. Longitudinal variation was more important than seasonal in determining the species composition in both rivers, and the difference between seasons was not statistically significant. Altitude was the most important factor determining species distribution.
Keywords: Community ecology; Freshwater fish; Environmental factors; Neotropical rivers